Processing, Uses and Constraints to Edible Insect Consumption in Ekiti State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
Insects have played an important role in the history of human nutrition, especially as important sources of high protein. This study investigates the processing, uses and constraints to edible insect consumption in Ekiti State. The study area was stratified based on ecological zones into; tropical rainforest and derived savanna. Four local government areas were selected from each ecological zone, and two villages were selected from each LGA. Structured questionnaires were administered to twenty (20) respondents in each of the eight selected villages. Field observations revealed that the majority of the respondents were female (65%), with (48%) of them above 30 years and (41%) of the respondents were farmers. The result revealed that six (6) insects were consumed by the respondents in the study area, with Marcrotermes nigeriensis (31%) being the most consumed insect, followed by Rhynchophorus phoenicis (22%), Cirina forda (20%), while Gryllotalpa africana (6%) was the least consumed insect. The result on the functional values of edible insects revealed that (32%) of the respondents stated that edible insects are rich in protein, while (25%) consume insects as meat for a cheaper alternative source of protein. Another (18%) stated that edible insects are medicinal. The result shows that the commonly used processing method by the respondents is roasting (44%). Lack of knowledge of the nutritional values and seasonal availability were the major challenges against the consumption of edible insects in the study area. The study recommends creating public awareness about the health and nutritional benefits of these edible insects, alongside adopting improved processing and preservation techniques.